2021
DOI: 10.1017/dmp.2021.173
|View full text |Cite
|
Sign up to set email alerts
|

Self-Medication in the COVID-19 Pandemic: Survival of the Fittest

Abstract: After the WHO declaration of the COVID-19 pandemic intense scuffling against novel coronavirus was observed and established fatal in most regions of the world. High fatality rate and socioeconomic downfall affected the health of non victimized individuals and consequently, health care measures, scheduled clinical and hospital visits avoided by the population hence the adaptation of self-medication proved as the mere troubleshooter for the general population as a swift safeguard for the further possible vulnera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
4
10
0
2
Order By: Relevance
“…In this study, the extent of self-medication was found to be 73.6%, relatively similar to studies in Pakistan (64%), 43 Bangladesh (71.4%), 44 and Ethiopia (71.4%) 8 that were conducted in the analogous context of the COVID-19 pandemic, though greater than findings in Brazil (14.9%), 45 Tamil Nadu (17.8%), 46 Saudi Arabia (35.4%), 47 and India (35.1%). 14 Other results from Ethiopia in different towns further strengthen this difference: Welaita Soddo (33.7%), 48 Jijiga (37.5%), 2 Dessie (42.4%), 49 and Gonder (50.2%).…”
Section: Discussionsupporting
confidence: 89%
“…In this study, the extent of self-medication was found to be 73.6%, relatively similar to studies in Pakistan (64%), 43 Bangladesh (71.4%), 44 and Ethiopia (71.4%) 8 that were conducted in the analogous context of the COVID-19 pandemic, though greater than findings in Brazil (14.9%), 45 Tamil Nadu (17.8%), 46 Saudi Arabia (35.4%), 47 and India (35.1%). 14 Other results from Ethiopia in different towns further strengthen this difference: Welaita Soddo (33.7%), 48 Jijiga (37.5%), 2 Dessie (42.4%), 49 and Gonder (50.2%).…”
Section: Discussionsupporting
confidence: 89%
“…Lockdown and isolation guidelines have prevented the population from visiting hospitals and clinics and have altered health-seeking behavior. As different SARS-CoV-2 variants keep emerging, people are likely to self-medicate ( 48 ). Medical students are also probable to keep self-medicating, which could be helpful in obtaining benefits of self-care, and alleviating burden on the healthcare system of the country by reducing number of physician visits ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Based on a study in Pakistan during the pandemic’s peak, fear of being exposed to the coronavirus in hospitals and clinics increased to an extent that people preferred to avoid their routine clinic visits and consultancy and turn toward self-medication. This issue is specifically higher in people suffering from diseases such as diabetes, hypertension, allergy, digestive disorders, etc., compared to people with no diseases as they believe coronavirus exposure is a high risk to their condition [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings of SMA studies from EMR countries during COVID-19 report the prevalence of SMA practices spans from 20.8% to 45.8% [ 26 , 29 ]. Nonetheless, several factors led to the initiation of SMA [ 40 , 42 , 44 , 45 , 46 ]. Upon such bases, we suggest that SMA practices decreased during COVID-19, but the lack of sufficient studies reporting such in the EMR makes these findings inconclusive.…”
Section: Discussionmentioning
confidence: 99%